Nanotecnologia no agronegócio : um estudo econômico da "língua eletrônica" na cafeicultura - Koken, Fernanda Sobreira Cossate Van de (2006)
Following the Schumpeterian theoretical approach this work is founded in the conception that the world economic history is a history of technological revolutions. These revolutions are impel by the development of new products and new process of production and distribution that incessantly revolutionize the economic system “from inside”. In this context it is agued that the contemporary society lives the emergency of a new “technological paradigm” characterized for the convergence of innovations in the areas of nanotechnology, biotechnology, information technologies and cognition (the NBIC´s paradigm). This dissertation ransoms concepts and ideas of evolutionary economics about the innovative processes; describe and ransoms historically the nanotechnologies development; focuses an specific nanotechnological innovation: ‘the cyber tongue’ and finally discuss it’s function in coffees quality improvement program in Brazil.